Tendencias de investigación en formación permanente de profesores: estado del arte e interpretación de actores clave - Quintero Tapia, John Jamer; Miranda Jaña, Christian Esteban; Rivera Rivera, Pablo Javier (Universidad de Costa Rica, 2018)
The article reports the results on the research trends of the permanent formation of teachers (FPP) in Chile between 1997 and 2007. The study uses a sequential mixed methodology with equal status (quantitative -- qualitative), to analyze a corpus of 40 studies that were selected from 629 investigations. In addition, an in-depth interview was conducted with 4 key informants to triangulate the analysis of the selected studies. The main results indicate that: i. The FPP is understood from the terminological diversity and the concept of perfection (40% of the studies). The most used methodologies are qualitative (55% studies). ii. Qualitatively, it is described that: a) there is a conceptual polysemy about the conceptualization of FPP; b) there is a lack of methodological rigor in educational research presented at national level; c) the lack of communication of research results to teachers and designers of educational policy is exposed; d) criticism is expressed on the topics of fashion and interests of researchers. As a conclusion, we can observe conceptual changes in the fenomenon, but there is a lack of sincronicity between the demands of escolar world and the topic that are investigate (also the comunication mecanism of the research). As to the applicability of the results, the main trends found allow to problematice into topics, metodologies about the reasearchs that can be made about FPP.